2023
DOI: 10.1021/jacs.3c00589
|View full text |Cite
|
Sign up to set email alerts
|

Reversed Controlled Polymerization (RCP): Depolymerization from Well-Defined Polymers to Monomers

Abstract: Controlled polymerization methods are well-established synthetic protocols for the design and preparation of polymeric materials with a high degree of precision over molar mass and architecture. Exciting recent work has shown that the high end-group fidelity and/or functionality inherent in these techniques can enable new routes to depolymerization under relatively mild conditions. Converting polymers back to pure monomers by depolymerization is a potential solution to the environmental and ecological concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 109 publications
1
66
0
Order By: Relevance
“…In contrast, the design of depolymerizable polymers formed by addition across a C–C π bond, such as HDPE and i PP, poses a substantial challenge due their generally higher hydrolytic and thermodynamic stability . Nevertheless, over the past several years, it has been demonstrated that some specific C–C backbones, such as poly­(methyl methacrylate) (PMMA) ( T c of 205 and 296 °C at 1.0 and 9.35 M (bulk), respectively), prepared by controlled polymerization can be depolymerized under moderate conditions, presenting exciting opportunities for further innovations . This depolymerizability arises from the high-fidelity end-group functionality achieved through polymerization techniques including atom transfer radical polymerization (ATRP) and reversible addition–fragmentation chain-transfer (RAFT) polymerization …”
Section: Recent Developments In Depolymerizable Backbonesmentioning
confidence: 99%
“…In contrast, the design of depolymerizable polymers formed by addition across a C–C π bond, such as HDPE and i PP, poses a substantial challenge due their generally higher hydrolytic and thermodynamic stability . Nevertheless, over the past several years, it has been demonstrated that some specific C–C backbones, such as poly­(methyl methacrylate) (PMMA) ( T c of 205 and 296 °C at 1.0 and 9.35 M (bulk), respectively), prepared by controlled polymerization can be depolymerized under moderate conditions, presenting exciting opportunities for further innovations . This depolymerizability arises from the high-fidelity end-group functionality achieved through polymerization techniques including atom transfer radical polymerization (ATRP) and reversible addition–fragmentation chain-transfer (RAFT) polymerization …”
Section: Recent Developments In Depolymerizable Backbonesmentioning
confidence: 99%
“…Although pyrolysis of PMMA was reported to reach near-quantitative monomer recovery at 400–525 °C, very complex reactors were required to reduce the PMMA’s residence time within the reactor and prevent the primary radical species from undergoing side reactions. Recently, unzipping depolymerization of polymethacrylates was observed via reversible activation of the terminal C–X group (X = halogen or thioester). However, this approach requires high-end-group fidelity to achieve high efficiency, which would sacrifice molecular weight ( M n < 10 4 g/mol for PMMA) and material performance. …”
Section: Introductionmentioning
confidence: 99%
“…In terms of kinetics, the continuous consumption or formation of a monomer requires active chain ends. Therefore, controlled radical polymerization (CRP), also termed reversible deactivation radical polymerization (RDRP), emerges as a powerful tool for efficient depolymerization at moderately lower temperatures because of the preservation of the chain-end functionality (CEF), which can be harnessed to generate active radicals. , …”
mentioning
confidence: 99%
“…Among various RDRP methods, Atom Transfer Radical Polymerization (ATRP) and Reversible Addition–Fragmentation chain-Transfer (RAFT) polymerization techniques are most often used to prepare well-defined polymers with low dispersity. While RAFT polymers mainly bear dithiocarbonates, trithiocarbonates, and xanthates at their ω-chain ends, polymers prepared by ATRP contain halogens (i.e., Cl and Br) at the ω-chain ends. Polymethacrylates prepared by ATRP or RAFT have been depolymerized using various activators and/or catalysts at elevated temperatures. , Since the polymerization of monomers with bulky substituents is thermodynamically less favorable than those with the smaller ones, their depolymerization can be conducted at lower temperatures. Indeed, the first examples using ATRP were reported for limited/equilibrated polymerization of methacrylates with bulky POSS (polyhedral oligomeric silsesquioxanes) and then for depolymerization of polymethacrylates with large PDMS (poly­(dimethylsiloxane)) substituents (up to 79% depolymerization, Scheme A). , …”
mentioning
confidence: 99%